1991
DOI: 10.1007/bf00290663
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of nucleomorph-encoded eukaryotic small subunit ribosomal RNA in cryptomonads

Abstract: In cryptomonads, unicellular phototrophic flagellates, the plastid(s) is (are) located in a special narrow compartment which is bordered by two membranes; it harbours neither mitochondria nor Golgi dictyosomes but comprises eukaryotic ribosomes and starch grains together with a small organelle called the nucleomorph. The nucleomorph contains DNA and is surrounded by a double membrane with pores. It is thought to be the vestigial nucleus of a phototrophic eukaryotic endosymbiont. Cryptomonads are therefore supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…When plastid-containing cryptomonads were used in similar PCRs, two nuclear-type srRNA gene products were recovered (Douglas et al, 1991b;McFadden et al, 1994). One product is from the host nuclear srRNA genes, while the other is from the endosymbiont nucleomorph genome (Douglas et al, 1991b;Maier et al, 1991;McFadden et al, 1994). Previous electron microscopy analyses found no trace of any endosymbiont in Goniomonas (Kugrens & Lee, 1991), and the PCR analysis undertaken here indicates that no endosymbiont srRNA genes are present in Goniomonas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When plastid-containing cryptomonads were used in similar PCRs, two nuclear-type srRNA gene products were recovered (Douglas et al, 1991b;McFadden et al, 1994). One product is from the host nuclear srRNA genes, while the other is from the endosymbiont nucleomorph genome (Douglas et al, 1991b;Maier et al, 1991;McFadden et al, 1994). Previous electron microscopy analyses found no trace of any endosymbiont in Goniomonas (Kugrens & Lee, 1991), and the PCR analysis undertaken here indicates that no endosymbiont srRNA genes are present in Goniomonas.…”
Section: Resultsmentioning
confidence: 99%
“…A biflagellate host harbours a photosynthetic endosymbiont (Maier et al, 1991;Douglas et al, 1991b). Although much reduced, the eukaryotic endosymbiont retains its nucleus and cytoplasm (McFadden et aL, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the cryptophyte algae arose when a eukaryotic protist engulfed a eukaryotic alga related to red algae which became an endosymbiont Maier et al, 1991). An ancestral rhodophyte also seems to be the origin of heterokont plastids and it has * Author to contact regarding correspondence and offprints.…”
Section: Introductionmentioning
confidence: 99%